ATP-sensitive potassium channels mediate survival during infection in mammals and insects. - Croker, B.; Crozat, K.; Berger, M.; Xia, Y.; Sovath, S.; Schaffer, L.; Eleftherianos, I.; Imler, J.L.; Beutler, B. (Nature Genetics, 2007)
Specific homeostatic mechanisms confer stability in innate immune responses, preventing injury or death from infection. Here we identify, from a screen of N-ethyl-N-nitrosourea-mutagenized mice, a mutation causing both profound susceptibility to infection by mouse cytomegalovirus and approximately 20,000-fold sensitization to lipopolysaccharide (LPS), poly(I.C) and immunostimulatory (CpG) DNA. The LPS hypersensitivity phenotype is not suppressed by mutations in Myd88, Trif, Tnf, Tnfrsf1a, Ifnb, Ifng or Stat1, genes contributing to LPS responses, and results from an abnormality extrinsic to hematopoietic cells. The phenotype is due to a null allele of Kcnj8, encoding Kir6.1, a protein that combines with SUR2 to form an ATP-sensitive potassium channel (K(ATP)) expressed in coronary artery smooth muscle and endothelial cells. In Drosophila melanogaster, suppression of dSUR by RNA interference similarly causes hypersensitivity to infection by flock house virus. Thus, K(ATP) evolved to serve a homeostatic function during infection, and in mammals it prevents coronary artery vasoconstriction induced by cytokines dependent on TLR and/or MDA5 immunoreceptors.